Pooled Analysis of Long-Term Survival Data From Phase II and Phase III Trials of Ipilimumab in Unresectable or Metastatic Melanoma - Schadendorf, Dirk; Hodi, F Stephen; Robert, Caroline; Weber, Jeffrey S; Margolin, Kim; Hamid, Omid; Patt, Debra; Chen, Tai-Tsang; Berman, David M; Wolchok, Jedd D (Journal of clinical oncology, 2015)
To provide a more precise estimate of long-term survival observed for ipilimumab-treated patients with advanced melanoma, we performed a pooled analysis of overall survival (OS) data from multiple studies. The primary analysis pooled OS data for 1,861 patients from 10 prospective and two retrospective studies of ipilimumab, including two phase III trials. Patients were previously treated (n = 1,257) or treatment naive (n = 604), and the majority of patients received ipilimumab 3 mg/kg (n = 965) or 10 mg/kg (n = 706). We also conducted a secondary analysis of OS data (n = 4,846) with an additional 2,985 patients from an expanded access program. OS rates were estimated using the Kaplan-Meier method. Among 1,861 patients, median OS was 11.4 months (95% CI, 10.7 to 12.1 months), which included 254 patients with at least 3 years of survival follow-up. The survival curve began to plateau around year 3, with follow-up of up to 10 years. Three-year survival rates were 22%, 26%, and 20% for all patients, treatment-naive patients, and previously treated patients, respectively. Including data from the expanded access program, median OS was 9.5 months (95% CI, 9.0 to 10.0 months), with a plateau at 21% in the survival curve beginning around year 3. To our knowledge, this is the largest analysis of OS to date for ipilimumab-treated patients with advanced melanoma. We observed a plateau in the survival curve, beginning at approximately 3 years, which was independent of prior therapy or ipilimumab dose. These data add to the evidence supporting the durability of long-term survival in ipilimumab-treated patients with advanced melanoma.